Limiting amino acids sorghum grain protein for adult female swine - Thulin, A.J.; Allee, G.L.; Pollman, D.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two 4 x 4 Latin square designs were used with 16 gilts at 10 mo of age and weighing 341 lb (gravid) and 301 lb (nongravid) to determine the limiting nitrogenous factors in sorghum grain protein for adult gravid (70th day postcoitum) and nongravid swine. Supplementation of the fortified sorghum grain diet with lysine increased (P<.05) nitrogen retention in both nongravid and gravid gilts. A further addition of threonine also increased (P >.05) nitrogen retention in both nongravid and gravid gilts. However, addition of both lysine and threonine to the sorghum diet failed to result in nitrogen retention equal to that observed for the control diet. Percentage of nitrogen digested was higher (P<.05) for the control diet than for the basal diet or the two diets with lysine and threonine added. Blood urea nitrogen was reduced (P<.05) when lysine was added to the basal diet with an additional reduction when threonine also was added to the diet. However, the control diet caused higher blood urea values when compared to both supplemented diets. These results suggest that another amino acid may be limiting in the sorghum grain diet supplemented with both lysine and threonine. These data and other published data demonstrate that lysine and threonine are the first and second limiting amino acids in sorghum grain for adult gravid and nongravid swine.
Keywords: Swine; Amnio acids; Sorghum; Protein